Subtidal Marine Algal Community and Endangered Species in Dokdo and Ulleungdo, Two Oceanic Islands in the East Sea of Korea - Jung, Seung Wook; Oh, Yoon Sik; Rho, Hyun Soo; Choi, Chang Geun (Ocean science journal, 2020)
Dokdo and Ulleungdo islands harbor diverse marine algae and are therefore uniquely well-suited for research on marine algae distribution and ecological changes. However, these two islands are largely inaccessible and thus their associated marine ecosystems are much less studied than other regions. Therefore, our study sought to examine the species composition and biomass of subtidal marine algae at 11 locations in both islands in the spring of 2014. A total of 164 species comprising 20 green, 48 brown, and 96 red algae, were identified, and these were classified into three phyl a, 50 families, and 100 genera. Cluster analysis and non-metric multidimensional scaling plots revealed that all surveyed sites except the Landing place and Hokdomgul (Dokdo) were similar in species composition. Community indices were measured based on the biomass of the collected species. The abundance index ranged from 10.57 to 23.19, and the evenness index ranged between 0.21 and 0.48. The diversity index was high (4.70) in Neunggeol, Ulleungdo, and low (3.69) in Hokdomgul, Dokdo. The present study provides baseline data for the conservation of subtidal communities and endangered species, as well as for future monitoring of changes in subtidal vegetation in response to global warming.